Calretinin: from a “simple” Ca2+ buffer to a multifunctional protein implicated in many biological processes - Schwaller, Beat (Frontiers in Neuroanatomy, 2014)
The hexa-EF-hand Ca2+-binding protein calretinin (CR) is predominantly expressed in specific neurons of the central and peripheral nervous system. However, CR expression is also observed in non-neuronal cells, e.g., during embryonic development and in mesothelioma cells. Of the 6 EF-hand domains, 5 are functional; the first 4 domains form 2 pairs showing high cooperativity within a pair that results in non-linear modulation of intracellular Ca2+ signals by CR. EF-hand domain 5 has a low affinity and represents the identified interaction site with CR-binding partners present in mouse cerebellar granule cells. CR binding to other targets including the pore-forming α1 subunit of the Ca2+ channel CaV2.1, as well as to huntingtin indicates additional Ca2+ sensor functions besides the well-known Ca2+-buffering functions. The absence of CR in cerebellar granule cells of CR−/− mice results in increased excitability and altered firing of Purkinje cells and promotes cerebellar 160-Hz oscillations impairing motor coordination. The putative role of CR in neuroprotection is still highly discussed. Altogether, CR emerges as a multi-functional protein also associated with development, i.e., cell proliferation, differentiation, and cell death.